Efektivitas Penggunaan Mulsa Plastik dalam Meningkatkan Produktivitas Tanaman Cabai (Capsicum annuum L.) - Apriyangsa Gulo; Listari Harefa; Fitri Julianti Gea (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Chili (Capsicum annuum L.) is a high-value horticultural commodity, but its productivity is often hampered by factors such as soil conditions, climate, pests and disease. The use of plastic mulch, especially the black-silver type, can increase chili yields by 25–40% through weed control, maintaining soil temperature, and reducing evaporation. Although initial costs are relatively high, significant yield increases can offset those costs. However, the resulting plastic waste is an environmental problem, so biodegradable mulch can be a more environmentally friendly alternative. This research uses a literature review method to collect and evaluate information from various relevant sources regarding the application of plastic mulch in increasing chili productivity. With proper management, plastic mulch can support increased chili yields and agricultural sustainability.